Repeatability and Inter-device Agreement for Three Different Methods of Keratometry: Placido, Scheimpflug, and Color LED Corneal Topography - Hidalgo, Irene Ruiz; Rozema, Jos J.; Dhubhghaill, Sorcha Ní; Zakaria, Nadia; Koppen, Carina; Tassignon, Marie-José (Journal of refractive surgery (1995), 2015)
PURPOSE: To determine the repeatability of a color LED corneal topographer (Cassini; iOptics, The Hague, The Netherlands) and compare it with Placido and Scheimpflug based devices (EyeSys 2000; EyeSys Laboratories, Houston, TX, and Pentacam HR; Oculus Optikgeräte GmbH, Wetzlar, Germany). METHODS: This prospective study involved 20 healthy volunteers (20 eyes) recruited from the staff of the Antwerp University Hospital. For each eye, three measurements were taken using each device, from which eight parameters describing keratometry and astigmatism were derived. Repeatability was assessed using intrasession, within-subject analysis of variance. Agreement was evaluated between pairs of devices with Bland– Altman plots and 95% confidence intervals. RESULTS: The repeatability values were good for all three devices, although slightly worse for the Cassini than for the other two devices for steep, flat, and mean keratometry. The EyeSys showed worse repeatability for the astigmatism axis. EyeSys and Pentacam agreed well with each other in terms of mean keratometry, whereas the Cassini gave consistently higher values by 0.52 diopters (D) when compared with the EyeSys (The repeatability values were good for all three devices, although slightly worse for the Cassini than for the other two devices for steep, flat, and mean keratometry. The EyeSys showed worse repeatability for the astigmatism axis. EyeSys and Pentacam agreed well with each other in terms of mean keratometry, whereas the Cassini gave consistently higher values by 0.52 diopters (D) when compared with the EyeSys ( P < .05, paired t test) and by 0.38 D when compared with the Pentacam ( P < .05, paired t test). The Cassini provided similar repeatability values (2.31°) for the astigmatism axis to the Pentacam (2.22°), in contrast to the EyeSys, which produced much more variable axes (9.0°) ( P < .05, paired t test). CONCLUSIONS: Overall, the three devices display comparable repeatability. The one exception is the astigmatism axis measurement of the EyeSys. The Cassini provides higher keratometry values than the other two devices, but the astigmatism axis agrees well with that provided by the Pentacam. [[ J Refract Surg. 2015;31(3):176–181.]